Impact of Rapid Ventricular Pacing on Outcome After Transcatheter Aortic Valve Replacement. Issue 14 (17th July 2018) - Fefer, Paul; Bogdan, Andrada; Grossman, Yoni; Berkovitch, Anat; Brodov, Yafim; Kuperstein, Rafael; Segev, Amit; Guetta, Victor; Barbash, Israel M.
Abstract : Background: Rapid ventricular pacing (RVP) is used commonly during transcatheter aortic valve replacement (TAVR). Little is known about the safety and clinical consequences of this step. The aim of this study was to assess the impact of RVP on immediate and long‐term clinical outcomes in a large cohort of non‐selected TAVR patients. Method and Results: The study included 412 consecutive patients undergoing TAVR with a mean age of 82±7 years, of which 47% were male. Patients were divided according to the number of RVPs during the TAVR procedure comparing patients undergoing no pacing (0), 1 to 2, and ≥3 pacing episodes (3+). Patients undergoing 3+ pacing episodes were significantly more likely to develop new atrial fibrillation (5.6% versus 7.3% versus 15%, respectively, for 0, 1–2, and 3+ groups, P =0.047), acute kidney injury (AKI) (18% versus 18% versus 28%, respectively, P <0.001), prolonged procedural hypotension (0%, 16%, and 25%, respectively; P <0.001), and suffered greater in‐hospital mortality (1.7%, 1.7%, and 6.5%, respectively, P =0.045), and 1‐year mortality (11.1%, 7.7%, and 18%, respectively, P =0.015). Multivariate Cox regression analysis indicated that acute kidney injury (OR 3.27 [1.763–6.09], P <0.001), euroSCORE II (OR 1.06 per unit [1.01–1.12], P =0.03), and 3+ pacing episodes (OR 2.35 [1.18–4.7], P =0.02) were the only independent predictors for 1‐year mortality. Conclusions: In patients undergoing TAVR, multiple RVP episodes and prolonged RVP duration are associated with adverse outcomes including short‐ and long‐term mortality. Thus, operators should attempt to minimize the use of RVP, especially in patients who are at risk for post‐procedural acute kidney injury.